Progress in the genetic analysis of Parkinson's disease. (13th September 2019) - Singleton, Andrew; Hardy, John
Abstract: The pace of genetic discovery in complex disease has accelerated exponentially over the last decade. Our fund of knowledge of the foundational genetics in disease has never been as great. There is a clear path forward to the resolution of the genetic architecture toward a point at which we will saturate the biological understanding of disease through genetics. This understanding continues to provide fundamental insights into disease biology and, with the advent of new data and methodologies, the path from gene to function is becoming clearer and cleaner. In this opinion piece, we discuss progress in the genetics of Parkinson disease. We explore what genetics has revealed thus far in the context of disease biology. We highlight mitophagy/autophagy, dopamine metabolism and the adaptive immune system. We try and link these findings together to give a holistic view of pathogenesis with the underlying theme that disease pathogenesis relates to a failure of damage response pathways. In the 1990s, Parkinson's disease was regarded a non-genetic disorder. Since that time, however, a huge number of Mendelian loci and risk loci have been identified by positional cloning and by genome-wide association studies. In this review, it is not our intent to list each gene and locus and review their identification [Hernandez, D.G., Reed, X. and Singleton, A.B. (2016) Genetics in Parkinson disease: Mendelian versus non-Mendelian inheritance. J. Neurochem., 139 Suppl 1, 59–74] but rather to outline the pathogenetic mechanisms that these analyses are revealing and then, given the large number of loci already identified, to lay out what we hope future analyses may help us understand, both in terms of disease mechanisms and for risk prediction for the syndrome.